2011
DOI: 10.4236/ojog.2011.13029
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-resistant gestational trophoblastic neoplasia, 5-years experience of Mansoura University Hospital, Egypt

Abstract: Introduction: Gestational trophoblastic neoplasia (GTN), is recognized as the most curable gynaecologic malignancy. However, many cases are resistant to first line chemotherapy. Objective: The aim of the study is to report our 5 years experience in the management of GTN cases with special stress on the chemo-resistant cases. Methods: The study was performed through reviewing the records of 51 patients who were diagnosed as GTN during the period from 1/1/2006 to 31/12/2010 in Mansoura University Hospital, Egypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 19 publications
1
6
0
9
Order By: Relevance
“…Similar to our findings, several studies reported that the score and metastasis, β‐hCG level, mass size and distance from index pregnancy were the main prognostic factors . As expected, the most important factor was the disease score.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to our findings, several studies reported that the score and metastasis, β‐hCG level, mass size and distance from index pregnancy were the main prognostic factors . As expected, the most important factor was the disease score.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our findings, several studies reported that the score and metastasis, β-hCG level, mass size and distance from index pregnancy were the main prognostic factors. 2,3,[18][19][20][21][22] As expected, the most important factor was the disease score. In our study, patients with a score of 5 and 6, which is commonly known as the intermediate risk group, had a 14-fold higher risk of resistance to single-agent chemotherapy, compared with the low-risk group (score, ≤4).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This is also seen in majority of the studies. 4,5 Metastases were present in 33.64% of cases and the most common site was lungs (72.22%).…”
Section: Discussionmentioning
confidence: 99%